리앙(李昻)의 『화장한 피의 위령제(彩妝血祭)』를 통해 본 애도의 정치 - 김순진; Kim Soon Jin (중국연구, 2019)
“A Powdered Bloody Sacrifice for Departed Souls,” Li Ang’s novella published in 1997, is a narrative of mourning for the victims killed in the February 28th Incident of 1947 and by the subsequent white terror. At the same time, it is a narrative of consolation and hope for the survivors burdened to mourn the departed. We find two axes in the story. A family memorial service for consoling the souls is one axis, and the pain and discord surrounding the family history of Mother Wang who leads the opposition is the other. The juxtaposition of a “private” family memorial service and a “public” sacrifice for the departed souls of the “February 28th” victims is related to the narrative structure that employs two narrators: the main narrator and a co-narrator. It is also related to the “death photos” that exist only as hearsay. The truthfulness of the photos is emphasized more by not turning up, and that leads to a realization that the truth remains placed in an oppressive environment. This helps foster the spirit of resistance and solidarity. The suicide of Mother Wang in “A Powdered Bloody Sacrifice for Departed Souls” can be seen as the result of the remorsefulness for not having protected her son from the violence of the powerful, and of the double guilty conscience about her husband and her son. She casts her body as an expression of her wishes that the lamp that bears three names, those of her diseased uncle died in the February 28th, of her husband and her son killed in the white terror, may drift afar. This demonstrates her wishes for the realization of justice and the revelation of historical truth. “A Powdered Bloody Sacrifice for Departed Souls” by Li Ang is consistent with Judith Butler’s idea for transforming the sorrow of a community into the power of political activity. Mourning for the departed in a world of violent oppression is bound to be postponed indefinitely. It might even be said that the mourner becomes the object of the mourning. The sorrow that can be expressed only by suicide calls for a clearer, louder voice of the community. “A Powdered Bloody Sacrifice for Departed Souls” is a response to such a calling.